Empiric Treatment of Focal Organizing Pneumonia in a Patient with a Low-Risk Lung Mass - Mir Alikhan; Srihari Veeraraghavan (Case Reports in Pulmonology)
The authors present a case of a 57-year-old man presenting with a solitary lung mass. Transbronchial biopsy showed an organizing pneumonia pattern. A therapeutic trial of corticosteroids resulted in complete resolution avoiding surgery. The authors discuss the diagnosis of focal organizing pneumonia without surgical resection.